2005
DOI: 10.3748/wjg.v11.i29.4497
|View full text |Cite
|
Sign up to set email alerts
|

Liver-specific gene expression in mesenchymal stem cells is induced by liver cells

Abstract: The results indicate that (1) rat MSC from bone marrow can differentiate towards hepatocytic lineage in vitro, and (2) that the microenvironment plays a decisive role for the induction of hepatic differentiation of rMSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 46 publications
0
69
1
3
Order By: Relevance
“…14 Hence, it will be adequate to avoid growth factors for clinical applications, as HGF paracrine signaling may contribute to tumorigenesis in vivo 15 ; nonetheless, hepatic differentiation of MSCs without growth factors has not been reported to date. It was found that hepatocyte-specific gene expression in MSCs was induced by coculture with liver cells, 16 suggesting that liver cell coculture system with direct cell-to-cell contact has a stimulatory effect for differentiation of stem cells into hepatocytic lineage and is an optimal environment in vitro for differentiation induction. However, these direct coculture systems may cause difficulty to selectively sort differentiated stem cells for transplantation.…”
mentioning
confidence: 99%
“…14 Hence, it will be adequate to avoid growth factors for clinical applications, as HGF paracrine signaling may contribute to tumorigenesis in vivo 15 ; nonetheless, hepatic differentiation of MSCs without growth factors has not been reported to date. It was found that hepatocyte-specific gene expression in MSCs was induced by coculture with liver cells, 16 suggesting that liver cell coculture system with direct cell-to-cell contact has a stimulatory effect for differentiation of stem cells into hepatocytic lineage and is an optimal environment in vitro for differentiation induction. However, these direct coculture systems may cause difficulty to selectively sort differentiated stem cells for transplantation.…”
mentioning
confidence: 99%
“…This suggests that the potential role of CD44 in MSCs migration is represented in CD44 and hyaluronic acid interaction. Some researchers have reported that stem cells can regenerate various cell lineages by trans-differentiation or by a recovery through a mechanism of protection (Lange et al,2005).…”
Section: Discussion:-mentioning
confidence: 99%
“…2,3 In particular, MSCs can differentiate into hepatocyte-like cells through a specific cell-signaling pathway upon stimulation with a combination of hepatocyte growth factor (HGF), fibroblast growth factor, epidermal growth factor and other cytokines. [4][5][6] However, in a culture of human bone marrowderived MSCs (BM-MSCs) and hepatocytes, BM-MSCs that undergo hepatic differentiation probably account for only a small percentage of the population, 7 and any differentiation may not significantly change the outcome of the bone marrow stromal cell (BMSC) and hepatocyte coculture experiments. 8 MSCs have recently emerged as promising candidates for cell-based immunotherapy because these cells can modulate the immune responses in various ways.…”
Section: Therapeutic Mechanism Of Msc Transplantationmentioning
confidence: 99%